LAPORAN KEUANGAN MASJID ABU BAKAR SARI DITINJAU DARI ISAK NO 35 TENTANG PENYAJIAN LAPORAN KEUANGAN ENTITAS BERORIENTASI NONLABA - Nadila Nadila; Addiarahman Addiarahman; Marissa Putriana Marissa Putriana (Journal of Islamic Accounting Competency, 2026)
This research is entitled  “The Financial Report of Masjid Abu Bakar Sari Reviewed from ISAK 35 Concerning the Presentation of Financial Statements for Non-Profit Oriented Entities.” The purpose of this research is to examine the process of preparing financial reports at Masjid Abu Bakar Sari and to identify the factors that have led to the non-implementation of ISAK 35. This study employs a qualitative approach, aiming to present information, facts, and data regarding the financial reporting practices applied by Masjid Abu Bakar Sari. The data collection methods used in this research include observation, interviews, and documentation. The findings reveal that the mosque has not implemented ISAK 35 due to the lack of knowledge among its administrators regarding the standard. The financial reports are currently prepared in a weekly journal format using Microsoft Excel, which is considered by the management to be sufficient in meeting both internal and public informational needs. There are three main factors hindering the implementation of ISAK 35: (1) limited human resources and understanding of accounting standards, (2) the absence of guidance or training from external parties, and (3) low public demand for formal financial statements, as religious donations are primarily seen as acts of worship.